A Comparison Between Different Properties of Bromoxynil and Dichlobenil by DFT Method - grewal, R.P. Singh; sharma, Girija (Asian Journal of Biological and Life Sciences, 2017)
In this work, we perform a set of quantum mechanical calculations on compounds bromoxynil and Dichlobenil. Various properties bond length, dipole moment, energy, HOMO-LUMO energy gap studied by using DFT method in Gaussian calculations. The stability and chemical reactivity have been studied.
Keywords: DFT; Dipole moment; HOMO-LUMO; Nitrile Herbicides